Desempenho produtivo de vacas Holandês x Zebu em pastagens de gramíneas tropicais sob lotação rotacionada - Fukumoto, Nelson Massaru (2007)
This study was carried out at Experimental Santa Mônica Experimental Station belonged to, Embrapa Gado de Leite, in Rio de Janeiro State, Brazil, to evaluate: 1) agronomic and nutritive characteristics of three tropical grasses; 2) stocking rate, feed intake and body weight variation, and 3) milk yield and composition of crossbred cows (Holstein x Zebu) managed in a rotational grazing system. The treatments were: tanzaniagrass (Panicum maximum cv. Tanzânia), stargrass (Cynodon nlemfuensis cv. Estrela Africana) and marandugrass (Brachiaria brizantha cv. Marandu), managed with 30 days of resting period and three days of paddock occupation. The pastures were fertilized during the rainy season with 1,000 kg/ha/year using the 20:05:20 formula. The experimental design was a completely randomized block with two replications. Each replication consisted of one hectare area. The area of each paddock was 909 m2. Four experimental dairy cows were used for each replication and if necessary extra cows were used to offer 7% of green dry matter forage availability in relation to the body weight. The animals were individually supplemented with 2 kg/day of concentrate. There were no treatments differences (P>.05) for pre-grazing forage mass, pos-grazing forage mass and for dry matter availability, but there was a period effect (P<.05). The lowest values of dry matter availability were observed in the last experimental period, due to the rainfall shortage, low temperatures and photoperiod effects. The average nutritional values of pre-grazing forage mass were not different (P>.05) between the tropical grasses, but, the dry matter percentage was lowest (P<.05) in the tanzaniagrass (18.5%) and the crude protein was higher (P<.05) in the stargrass (11.3%). Tanzaniagrass (48.4%) showed the highest (P<.05) leaf blade percentage. The crude protein content of the hand-plucked samples was lower (P<.05) in the marandugrass (10.0%), but, it presented a high (P<.05) proportion of N as B1+B2 (46.3%) fractions. There was no treatment effect (P>.05) for milk yield and composition among the grasses. The average milk yield was: 9.1; 9.1 and 8.7 kg/cow/day for tanzaniagrass, stargrass and marandugrass, respectively. There were also no treatments difference (P>.05) for stocking rate, and the average stocking rate were: 4.6; 4.5 and 5.0 UA/ha for tanzaniagrass, stargrass and marandugrass, respectively. The cows managed on tanzaniagrass (2.6%) showed a higher (P<.05) dry matter intake, however, there was no treatment difference (P>.05) between stargrass (2.3%) and marandugrass (2.4%). Average body weight gain did not differ (P>.05) among treatments. In conclusion, the three tropical grasses, managed under the conditions of this study, presented similar milk yield potential.